Pengaruh Panjang Tungkai Terhadap Ketepatan Servis Dalam Permainan Sepak Takraw Pada Siswa Putra Kelas VIII Smpn 1 Dompu - Sandi Achmad Pratama; Linda Susila (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
This study aims to examine the effect of leg length on service accuracy in sepak takraw among male eighth-grade students at SMPN 1 Dompu. The research is grounded in the premise that anthropometric factors, particularly leg length, play a crucial role in supporting the execution of accurate service techniques. A quantitative approach with a comparative design was employed. The sample consisted of 24 students, categorized into two groups based on leg length (≥ or >92.25 cm). Research instruments includedanthropometric measurements and a standardized sepak takraw service accuracy test based on Nurhasan (2020). Data were analyzed using an independent sample t-test, which revealed a statistically significant difference between students with longer legs and those with shorter legs (t-value = 2.518 > t-table = 2.069; p < 0.05). Students with longer legs demonstrated better service accuracy than their shorter-legged counterparts.These findings suggest that leg length is a key physical characteristic to consider in training foundational sepak takraw techniques. This research is expected to contribute to the development of physical education strategies that are tailored to the individual physical profiles of students.